The Safety of Substitution of Antiretroviral Regimen in Non-Clinical Trial Settings in Asian Countries. (4th October 2017) - Jung, In Young; Boettiger, David; Wong, Wingwai; Lee, Man Po; Kiertiburanakul, Sasisopin; Chaiwarith, Romanee; Avihingsanon, Anchalee; Tanuma, Junko; Kumarasamy, N; Kamarulzaman, Adeeba; Zhang, Fujie; Kantipong, Pacharee; et al.
Abstract: Background: Although substitutions of antiretroviral regimen are generally safe, most data on substitutions are based on results from clinical trials. The objective of this study was to evaluate the safety of substituting antiretroviral regimen in virologically suppressed HIV-infected patients in non-clinical trial settings in Asian countries. Methods: HIV-infected patients enrolled in the TREAT Asia HIV Observational Database (TAHOD) were included in this analysis if they started combination antiretroviral therapy (cART) after 2002, were being treated at a center that documented a median rate of viral load (VL) monitoring ≥ 1 tests/patient/year, and experienced a minor or major treatment substitution while on virally suppressive cART (VL < 200 copies/mL). Minor regimen substitutions were defined as within-class changes and major regimen substitutions were defined as changes to a drug class. Virologic failure was defined as having had two viral load measurements > 400 copies/mL. The patterns of substitutions and rate of virologic failure after substitutions were analyzed. Results: Of 3, 994 adults who started ART after 2002, 3, 119 (78.1%) had at least one period of virological suppression. Among these, 1, 170 (37.5%) underwent a minor regimen substitution, and 296 (9.5%) underwent a major regimen substitution during suppression. The rates of virological failure were 1.48/100person years (95% CI 1.14–1.91) in the minor substitution group and 2.85/100person years (95% CI 1.88–4.33) in the major substitution group, and 2.53/100person years (95% CI 2.20–2.92) among patients that did not undergo a treatment substitution. Conclusion: The rate of virological failure was relatively low in both major and minor substitution groups, showing that regimen substitution is generally safe in non-clinical trial settings in Asian countries. Disclosures: All authors: No reported disclosures.